Volatility Dynamics of Rupiah Exchange Rate and Jakarta Composite Index During Indonesia's 2014-2019 Presidential Election Cycle - Hutabarat, Arnold; Damanik, Darwin (Program Studi Ekonomi Pembangunan Fakultas Ekononomi Universitas Simalungun, 2025)
Indonesia's 2014 and 2019 presidential elections provided a natural experiment for evaluating how large-scale political events propagate through emerging market financial systems. This research investigates the joint volatility behavior of the Indonesian Rupiah (IDR) and the Jakarta Composite Index (JCI) from 2014 to 2019, covering two complete electoral cycles with same candidates. Using daily data, event research design, and GARCH-family specifications, we document three core findings. First, both markets have developed better capabilities in managing political uncertainty and decreased volatility sensitivity during the 2014 and 2019 election periods. Second, leverage effects remain significant in both periods, showing that markets became more balanced in responding to positive and negative news, or in other words, there was increasing in market maturity and informational efficiency. Third, volatility in the 2014 period shows sharper patterns compared to 2019, reflecting market learning and adaptation to political risk patterns and may reducing political risk premiums over time